Uneven Playing Field: Insurance Status Adversely Affects Children with Tibial Spine Fractures (181). Issue 10 (31st October 2021) - Patel, Neeraj; Leska, Tomasina; Ganley, Theodore; Aoyama, Julien; Cruz, Aristides; Ellis, Henry; Fabricant, Peter; Green, Daniel; Jagodzinski, Jason; Johnson, Benjamin; Kushare, Indranil; Lee, R; et al.
Objectives: Previous studies have reported disparities in medical and surgical care resulting from demographic factors, including insurance status. Tibial spine fractures are uncommon injuries, which may exacerbate potential disparities in care. The purpose of this study is to assess the impact of insurance status on the treatment of tibial spine fractures in children and adolescents. Methods: We performed a retrospective cohort study of tibial spine fractures treated at 10 institutions between 2000 and 2019. Polytraumas and patients older than 18 years were excluded. Demographic data was collected as was information regarding pre-operative, intra-operative, and post-operative treatment, with attention to delays in management and differences in care. Both surgical and non-surgical fractures were included, but a separate analysis of operative patients was performed subsequently. Univariate analysis was followed by purposeful entry multivariate regression to adjust for confounding factors. Results: Data was collected on a total of 434 subjects with a mean age of 11.7±3.0. Of these, 61.1% had commercial insurance and 38.9% had public insurance. Publicly insured children were more likely to be injured in a motor vehicle accident. Among athletes, those with public insurance were injured more frequently during football while commercially insured patients were more likely to be injured while skiing. When analyzing the overall cohort of surgical and non-surgical fractures in multivariate analysis, those with magnetic resonance imaging (MRI) performed 21 or more days after injury were 5.3 times more likely to have public insurance (95% CI 1.3-21.7, p=0.02). Similar results were found with the 365 patients that required surgery. In this cohort, those with MRI delayed ≥21 days from injury were 4.8 times more likely to have public insurance (95% CI 1.2-19.6, p=0.03). Children that underwent surgery ≥21 days after injury were 2.2 times more likely to have public insurance (95% CI 1.1-4.1, p=0.02). Those that were publicly insured had 2.5 times higher odds of undergoing open surgery rather than arthroscopic (95% CI 1.1-6.1, p=0.04). These children also had 4.5 times lower odds of receiving a continuous passive motion machine (CPM) after surgery (95% CI 1.7-11.7, p=0.002) and were 4.0 times more likely to be immobilized in a cast rather than a brace post-operatively (95% CI 2.0-8.2, p<0.001). Conclusions: Children with public insurance and a tibial spine fracture were more likely to experience delays with MRI and surgical treatment than those with commercial insurance. Additionally, these patients were more likely to undergo open surgery and post-operative casting and less likely to receive a CPM machine.